2018
DOI: 10.1371/journal.pgen.1007623
|View full text |Cite
|
Sign up to set email alerts
|

AMPK signaling linked to the schizophrenia-associated 1q21.1 deletion is required for neuronal and sleep maintenance

Abstract: The human 1q21.1 deletion of ten genes is associated with increased risk of schizophrenia. This deletion involves the β-subunit of the AMP-activated protein kinase (AMPK) complex, a key energy sensor in the cell. Although neurons have a high demand for energy and low capacity to store nutrients, the role of AMPK in neuronal physiology is poorly defined. Here we show that AMPK is important in the nervous system for maintaining neuronal integrity and for stress survival and longevity in Drosophila. To understand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…We found that the genes associated with the top 30% SNPs were significantly enriched in eight pathways involved in regulating nervous system functions. For example, Axon guidance and AMPK signaling pathways identified in this work were proved to be linked to SCZ and bipolar BPD [15].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…We found that the genes associated with the top 30% SNPs were significantly enriched in eight pathways involved in regulating nervous system functions. For example, Axon guidance and AMPK signaling pathways identified in this work were proved to be linked to SCZ and bipolar BPD [15].…”
Section: Introductionmentioning
confidence: 74%
“…Besides, the nicotine addiction and AMPK signaling pathways were found to be related to the activity of neurotransmitters in the brain [15], [69]. People with a symptom of severe depression, schizophrenia, or bipolar disorder commonly had signs of a circadian entrainment disorder [70].…”
Section: G Snp Driven Pathway Enrichment Analysismentioning
confidence: 99%
“…Drosophila sleep has been rigorously examined and found to exhibit several of the mammalian hallmarks of sleep, such as sustained periods of quiescence, increased arousal threshold, and circadian and homeostatic regulation [13,14]. Indeed, recent studies in Drosophila have identified genes associated with human neurodevelopmental and psychiatric disorders that disrupt sleep and circadian rhythm, such as the candidate autism-spectrum-disorder gene Cullin-3 (Cul3) [15,16] and the gene alicorn (alc) linked to the 1q21.1 deletion, another deletion that confers schizophrenia risk [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to speculate that this mechanism might also contribute during sleep, when breathing slows and central energy reserves are replenished. Indeed, knockdown of AMPK in the central nervous system of the fruit fly Drosophila melanogaster led to disturbances in sleep patterns and to poorer recovery from sleep deprivation [101].…”
Section: Ampk and Central Neural Control Mechanismsmentioning
confidence: 99%